Compassionate medical approaches to breaking bad news: Strategies and impacts (Research, Society and Development, 2024)
This narrative literature review provides insight into the communication of bad news, with a primary focus on evaluating its impact on medical students. In the employed methodology, 48 studies were compiled, with seven selected for in-depth discussion, all published within the last five years. This review highlights that medical schools often lack theoretical and practical preparation for future physicians in delivering negative news. Furthermore, recognizing that the communication of bad news affects not only recipients but also those delivering the news, the study reveals various methods of conveying bad news and their applicability, such as outcomes and relevance, to ensure effective and comfortable communication for all parties involved. The study also delves into current protocols and their specificities, providing a comprehensive view of how they can be applied in situations involving the communication of bad news, emphasizing their utility and importance in the context of medical education. In summary, this work aims to review the most relevant aspects of the topic present in the literature and consolidate the main protocols developed to facilitate the communication of difficult news by healthcare professionals.